Exploring adolescents’ multimodal literacy as critical and creative prosumers in digital game-based multimodal composition - Shen, Yanan; Ab Jalil, Habibah; Jamaluddin, Rahimah (International Forum of Educational Technology and Society,National Taiwan Normal University, 2025)
Digital gameplay and digital multimodal composition (DMC) are promising multimodal literacy practices. Nevertheless, research on their incorporation in literacy classrooms to foster students’ multimodal literacy skills is lacking. This qualitative case study explored how two groups of Chinese adolescents used multimodal literacy in digital game-based multimodal composition and assumed their role as critical and creative prosumers. Through a 16-session project, the participants used tablets to collaboratively produce short game videos based on design resources obtained during their digital gameplay. The students demonstrated multimodal literacy through understanding, interpreting and applying multimodal semiotic modes for representational, interpersonal, and compositional meaning-making. Furthermore, they played a multifaceted role as prosumers, including critical gamers, reflective video editors, creative designers, and knowledgeable contributors to the gaming community. This study suggested that incorporating digital games for DMC practice is a valuable opportunity for multimodal literacy learning, cultivating students’ criticality and creativity for active participation in the digital era.